Iron, zinc, and protein bioavailability proxy measures of meals prepared with nutritionally enhanced beans and maize - Pachón, Helena; Ortíz, D.A.; Araújo, C; Blair, Matthew W.; Restrepo, J. (2009)
Nutritionally enhanced beans (NEB) with more Fe and Zn than conventional beans (CB) and nutritionally enhanced maize (NEM) with more tryptophan and lysine than conventional maize (CM) were developed as part of a crop-biofortification strategy to improve human nutrition. Proxy measures were used to assess Fe and Zn bioavailability and protein digestibility of a bean recipe (fríjol sancochado) and a maize-milk recipe (mazamorra) prepared with enhanced or conventional crops in Colombia. Fe concentration was similar in the cooked NEB and CB and in NEM and CM (P> or = 0.05); in vitro Fe dialyzability was similar in cooked NEB (9.52%) and CB (9.72%) and greater for NEM (37.01%) than CM (32.24%). Zn concentration was higher in the uncooked and cooked NEB than in the CB (P < 0.05); phytate: Zn molar ratios were high in cooked NEB (36: 1) and CB (47: 1), suggesting low Zn bioavailability, and not different from each other (P = 0.07). There were no differences in Zn concentration or phytate: Zn molar ratio in the maize recipes. Nitrogen, tryptophan, and lysine concentrations were higher in the cooked NEM than CM; nitrogen was higher in the cooked NEB than CB (P < 0.05). In vitro protein digestibility was comparable (82% to 83%) for NEM and CM and higher for NEB (84%) than for CB (82%). The higher nutrient concentrations + similar bioavailability (protein in NEM, Zn in NEB), same nutrient concentrations + higher bioavailability (Fe in NEM) or higher nutrient concentrations + higher bioavailability (protein in NEB) can translate into more nutrients absorbed and utilized by the body